Pengaruh Karakterisik Komite Audit terhadap Audit Report Lag: Studi Empiris pada Perusahaan Sektor Pertambangan Tahun 2021-2024 - Maulidia, Vina; Pebriyani, Dewi (Jurnal Eksplorasi Akuntansi, 2025)
This study aims to examine the effect of audit committee size, audit committee independence, and audit committee meeting frequency on audit report lag. The population in this study was mining companies listed on the Indonesia Stock Exchange (IDX) in 2021-2024. The research sample was determined using a purposive sampling method, with a sample size of 172 companies. The data used were secondary data from the companies' annual reports. The analytical method used was multiple linear regression analysis. The results showed that audit committee size had a positive effect on audit report lag, while audit committee independence and audit committee meeting frequency did not.